Phase-Shift Cyclic-Delay Diversity for MIMO OFDM Systems - Young-Han Nam; Lingjia Liu; Jianzhong (Charlie) Zhang (International Journal of Digital Multimedia Broadcasting)
Phase-shift cyclic-delay diversity (PS CDD) scheme and space-frequency-block-code (SFBC) PS CDD are developed for multiple-input-multiple-output (MIMO) orthogonal frequency division multiplexing (OFDM) systems. The proposed PS CDD scheme preserves the diversity advantage of traditional CDD in uncorrelated multiantenna channels, and furthermore removes frequency-selective nulling problem of the traditional CDD in correlated multiantenna channels.